Sperm protein profile and their correlation with frozen semen quality of indigenous Indonesian buffalo bulls - Said, Syahruddin; Maulana, Tulus; Iskandar, Hikmayani; Kaiin, Ekayanti Mulyawati; Khaerunnisa, Isyana; Putra, Widya Pintaka Bayu; Hasan, Fuad; Arifiantini, Raden Iis (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aimed to assess sperm motility characteristics, kinematic parameters, and sperm protein molecular weight (MW) in Indonesian buffalo to predict fertility. Materials and Methods: Frozen semen from Silangit (4 bulls), Murrah (4 bulls), and Toraya (2 bulls)—aged 7–10 years, was analyzed. Sperm motility was assessed using Computer Assisted Semen Analysis, viability and abnormality were evaluated using eosin-nigrosin staining, plasma membrane integrity was evaluated using the hypoosmotic swelling test, acrosomal status was evaluated using lectin peanut agglutinin, protamine deficiency was evaluated using chromomycin A3, and deoxyribonucleic acid (DNA) integrity was evaluated using Halomax. Protein concentration was determined using the bicinchoninic acid method and characterized with sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Results: The study revealed breed-specific variationsin semen quality. Silangit buffaloes exhibited lower DNA integrity, while Murrah buffaloes showed elevated motility and membrane integrity. Toraya buffaloes displayed higher normal morphology and protamine status, though they had lower viability. Notable differences in protein expression included the presence of SPAG9 and the absence of IZUMO1 in Toraya buffaloes. Protein MW analysis further showed correlations with sperm characteristics. In Murrah buffaloes, proteins within the 130–125 kilodalton (kDa) range were negatively correlated with acrosome integrity, whereas in Toraya buffaloes, proteins within the 55–50 kDa range were negatively correlated with sperm abnormalities. Silangit buffaloes showed a positive correlation between proteins at 32 kDa and sperm abnormalities. Conclusion: Analyzing protein MW through SDS-PAGE provides a promising approach for assessing semen quality in indigenous Indonesian buffalo bulls. Although the semen quality of the buffaloes in this study was variable, all bulls met the established Indonesian standards for semen quality and exhibited adequate fertilization potential. These results provide valuable insights into the reproductive biology of Indonesian buffalo bulls and form the basis for predicting fertility capacity through a comprehensive analysis of sperm characteristics and molecular profiles of sperm proteins. J. Adv. Vet. Anim. Res., 11(4): 846–855, December 2024 http://doi.org/10.5455/javar.2024.k836